2011
DOI: 10.1108/17508611111182395
|View full text |Cite
|
Sign up to set email alerts
|

Angels on the head of a pin

Abstract: Purpose -By proposing a comprehensive measurement framework, this paper attempts to move the nascent body of theoretical and empirical work on performance measurement in social entrepreneurship ventures (SEVs) into reach for practitioners. The purpose of this paper is to help social entrepreneurs and academics put current knowledge to work to gain usable feedback about the success of operations. Design/methodology/approach -This paper offers a framework for measuring firm survival, social action, and social ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The following ten models guided this framework: the framework for capability and integrative approaches (White, 2018), the performance measurement system model (Arena et al , 2015), the structural equation modelling of SI (Edwards et al , 2015), the sustainability, added value and scalability (Hadad and Găucă, 2014), the social performance framework (Ebrahim and Rangan, 2014), the analytical framework (Mouchamps, 2014), the multi-dimensional controlling model (Bagnoli and Megali, 2011), the economic survival framework (Lane and Casile, 2011), the four-category typology of alternative approaches (Polonsky and Grau, 2011), and the blended value accounting spectrum (Nicholls, 2009).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following ten models guided this framework: the framework for capability and integrative approaches (White, 2018), the performance measurement system model (Arena et al , 2015), the structural equation modelling of SI (Edwards et al , 2015), the sustainability, added value and scalability (Hadad and Găucă, 2014), the social performance framework (Ebrahim and Rangan, 2014), the analytical framework (Mouchamps, 2014), the multi-dimensional controlling model (Bagnoli and Megali, 2011), the economic survival framework (Lane and Casile, 2011), the four-category typology of alternative approaches (Polonsky and Grau, 2011), and the blended value accounting spectrum (Nicholls, 2009).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The multi-dimensional controlling model (Bagnoli and Megali, 2011) is suitable for small and medium-sized SEs with SEE goals, whereby the framework has three reference dimensions of control: economic and financial performance, social effectiveness and institutional legitimacy. Meanwhile, Lane and Casile’s (2011) economic survival framework provide SEs with measures for comprehensive performance measurement based on their respective organisational mission through using the survival, action and social change model. However, we found that the economic survival framework does not specify the firm size, although it does identify the SEE contributions.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…• Adaptability-works of authors such as Johanisova et al (2013), which investigated the adaptation of social businesses to economic crisis scenarios or degrowth, as well as other studies related to the dualistic nature of social and economic aims; a relevant legislation or proposing of a more adequate legal structure and other adaptations; • Entrepreneurship-articles that, despite having the keywords addressed in this study, only cite the subject and focus on the phenomenon of social entrepreneurship, as in Penedo and McLean (2006); • Social exclusion-studies involving social business with focus on marginalized groups, such as children and youth at situation of risk, people with mental disorders, or as in the research of Wilson (2012), communities with financial vulnerability and low-income consumers; • Management-works of author such as Lane and Casile (2011) who focused on the understanding or proposition of techniques and methods for improving business management. Some issues related to this category are management of organizational processes, strategies of resource allocation, management with indicators, and evaluation of the investment's social return; • Social intermediation-for instance, article written by Nwankwo et al (2007) who analyzed cases in which social businesses intermediate the relation between organizations interested in solving social problems and poor communities through plans of governmental initiatives, nonprofit entities, or related to corporate social responsibility; • Regionalisms-studies that comprehend business peculiarities of a particular country or region, or that use comparative studies among different regions, such as the Park and Wilding (2013) who compared government policy in UK and South Korea; • Profiles and skills-articles that reported features related to the profile of social entrepreneurs, construction and maintenance of organizational identity, satisfaction measurement, and work quality as well as specific skills observed in some enterprises analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Social impact assessment is complex because it often requires translating qualitative outcomes into quantifiable values (Grieco, 2015), and there is no single method to evaluate it (Lane and Casile, 2011). Measurement approaches include subjective scales (Schmitt and Alberton, 2022), non-financial reports, and tools such as social return on investment (SROI), social cost-benefit analysis (SCBA), social accounting and auditing system (SAA), social enterprise balanced scorecard (SEBS/SBSC), outcomes star (OS), social impact measurement for local economies (SIMPLE), uality first (QF), local multiplier 3 (LM3), among others (Cao, 2022;Grieco, 2015;Kah and Akenroye, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%